HUBUNGAN KELENTURAN DAN KEKUATAN OTOT TERHADAP KETERAMPILAN ROLL DEPAN SENAM LANTAI PADA SISWA KELAS X DI SMA TERUSAN BANGSA - Devi Berliana Hartati; Ferdi Zulkarnain; Nanda Dwicahya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Forward roll is a fundamental floor-gymnastics skill whose successful execution requires adequate physical conditioning, particularly flexibility and muscle strength. This study aimed to examine the relationship between flexibility and forward-roll skills, the relationship between muscle strength and forward-roll skills, and the simultaneous relationship of flexibility and muscle strength with forward-roll skills among Grade X students at SMA Terusan Bangsa. A quantitative correlational design was employed. The study involved all 26 Grade X students, consisting of 12 male and 14 female students, selected through total sampling. Flexibility was measured using the sit-and-reach test, while muscle strength was assessed using 60-second push-up and sit-up tests. Forward-roll performance was evaluated by two trained raters using an expert-validated assessment rubric covering the initial position, movement execution, and final position. Data were analyzed using descriptive statistics, Pearson product-moment correlation, multiple correlation, and the F-test with IBM SPSS Statistics version 25 at a significance level of 0.05. The results showed a positive and significant relationship between flexibility and forward-roll skills (r = 0.498; p = 0.0049) and between muscle strength and forward-roll skills (r = 0.655; p = 0.0001). Flexibility and muscle strength were also simultaneously associated with forward-roll skills (R = 0.655; R² = 0.428; F = 8.619; p = 0.0016). These findings indicate that muscle strength has a stronger association with forward-roll performance, while flexibility remains an important supporting component.